2020
DOI: 10.1186/s12882-020-02061-8
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in patients undergoing chronic kidney replacement therapy and kidney transplant recipients in Scotland: findings and experience from the Scottish renal registry

Abstract: Background Infection with the severe acute respiratory coronavirus 2 (SARS-CoV-2) has led to a worldwide pandemic with coronavirus disease 2019 (COVID-19), the disease caused by SARS-CoV-2, overwhelming healthcare systems globally. Preliminary reports suggest a high incidence of infection and mortality with SARS-CoV-2 in patients receiving kidney replacement therapy (KRT). The aims of this study are to report characteristics, rates and outcomes of all patients affected by infection with SARS-CoV-2 undergoing K… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
2
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 21 publications
3
31
2
3
Order By: Relevance
“…This is the first national study of hemodialysis patients with COVID-19 in Lebanon. Our results confirm the high mortality rate of this vulnerable population, as described in several previous reports from other countries [ 14 , 17 , 19 , 20 , 22 , 23 , 26 ]. Our patients’ death rate was estimated at 23.8%, very close to the 25% reported by the ERACODA study of 26 European and North Mediterranean countries including 768 dialysis patients [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…This is the first national study of hemodialysis patients with COVID-19 in Lebanon. Our results confirm the high mortality rate of this vulnerable population, as described in several previous reports from other countries [ 14 , 17 , 19 , 20 , 22 , 23 , 26 ]. Our patients’ death rate was estimated at 23.8%, very close to the 25% reported by the ERACODA study of 26 European and North Mediterranean countries including 768 dialysis patients [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…Patients with a kidney transplant, who are less likely to carry noted risk factors, require treatment with immunosuppressants, placing them at higher risk of severe COVID-19. 6 Registry reports in Europe have indicated that the fatality rate of COVID-19 among patients with ESKD is between 20% and 30%, [7][8][9][10] a range corroborated by single-center studies in the United States. 11,12 However, the initial effect of COVID-19 on population-level outcomes in the United States has not yet been assessed.…”
mentioning
confidence: 81%
“…Data from the Scottish Renal Registry suggest that measures introduced in early April to reduce this exposure, including the use of masks to and from dialysis and individual transport, were effective; with the number of cases in people receiving dialysis falling sharply two to three weeks before the rest of the general population within Scotland. 25 In order to capitalise on the utility of such knowledge in hospital-outbreak management, the results from the sequencing data need to be generated in a timely manner. 15 , 17 However, the feasibility of implementing this rapid sequencing response in the National Health Service to date has been impeded by lack of expertise and equipment for both high-throughput whole-genome sequencing and for processing the data generated into a form interpretable by infection control and public health.…”
Section: Discussionmentioning
confidence: 99%